Effective feature management : releasing and operating software in the age of continuous delivery - Kodumal, John (O'Reilly Media, 2018)
Feature flags give software organizations the power to reduce risk, iterate more quickly, and gain more control. This practical ebook explains how feature flags let you decouple feature rollout from code deployment--so you can control who sees what when, independent of release. John Kodumal, cofounder and CTO of the leading feature management platform LaunchDarkly, shows you how feature flags fit into your process, including how to combine them with blue-green deployments and branching. Ideal for developers, ops personnel, designers, product managers, and marketers, this guide teaches you how feature flags can unlock the true power of your software and enable you to deliver better results for your customers. You'll learn: How feature flags provide a decision point in your code that can change the behavior of your application Feature management use cases, including progressive delivery, infrastructure migrations, and experimentation and testing Best practices for incorporating feature management into your development process Requirements and considerations for selecting an enterprise-grade feature management platform How companies already using feature flags can apply advanced use cases, such as database migration.